Skyrmions in a half-filled second Landau level - Wójs, A; Möller, G; Simon, S; Cooper, N (2011)
We studied charged excitations of the ν=5/2 fractional quantum Hall state allowing for spin depolarization. It is generally accepted that the ground state is a spin-polarized incompressible quantum liquid, adiabatically connected to the Pfaffian state, whose spin-polarized quasiholes (QHs) obey non-Abelian statistics. Using numerical diagonalization and taking account of non-zero well widths we demonstrated that at a sufficiently low Zeeman energy it is energetically favorable for pairs of charge e/4 QHs to bind into charge e/2 Skyrmions. We showed that Skyrmion formation is further promoted by disorder, and argue that this can lead to a depolarized ground state in realistic experimental situations. © 2011 American Institute of Physics.